Measurements of pulsatile flow in an idealized ventricular assist device - Paciocco, Michael C (University of Ottawa (Canada), 2009)
Ventricular Assist Devices (VAD) are mechanical pumps connected to the human circulatory system in order to assist the left ventricle of diseased hearts in pumping blood to the body. Currently, both pulsatile and non-pulsatile VAD are used, primarily as a bridge to heart transplantation, with new generation devices under development to become alternatives to transplantation. Negative interactions between the biological components of the flow and the mechanical system, such as poor washout, recirculation, thrombosis and hemolysis need to be minimized in order to improve performance and longevity of both the device and the patient. The present research is an experimental study of flow in a highly idealized, diaphragm-type, pulsatile-flow VAD. Its objective is to document in detail the motions of the fluid and the diaphragm so that they can be used for the validation of ongoing numerical simulations of flows in such devices, and more generally to assist in validation of computational methods involving fluid-structure interaction. Measurements of the flow field were collected using both Laser Doppler Velocimetry (LDV) and Particle Image Velocimetry (PIV). The PIV system was used to measure the instantaneous velocity variation along each of six different planes at several different times during the cycle, whereas the two component LDV system was used to measure the time-dependent velocity at several points of interest over the entire cycle. The images recorded by the PIV system camera have also been used to determine the instantaneous shape and position of the diaphragm at different times during the cycle. Representative and averaged PIV images showed that the inlet jet created a core vortex in the VAD that is the primary means of mixing. The development and motion of this vortex over the VAD operational cycle was documented for use in future modelling. A previously unobserved vortex was also documented. This vortex appeared in the vertical plane, beneath the inlet jet at peak injection, and moved along the path of the jet during the injection phase. It is believed that this vortex is created by the interaction of the inlet jet and the diaphragm in motion during injection and represents a region of recirculation in the flow, as well as possible flow separation. Other regions of recirculation were identified in the area directly adjacent to the outlet jet during ejection of the flow, and along the surface of the VAD directly opposite of the outlet tube just prior to the beginning of the ejection cycle. Areas of stagnant flow were also observed, particularly in the inlet and outlet tubes in periods of inactivity. The flow during ejection was localized in the region of the VAD directly adjacent to the outlet tube. The ejection has a longer period and a lower peak velocity than the injection. The motion of the VAD diaphragm was also studied and it was found that the diaphragm deformation was influenced by the inlet jet. The diaphragm shape was nearly axisymmetric during some parts of the cycle, but highly skewed during other parts. Small-scale motions were also present in the diaphragm, and fluctuated from one cycle to another, adding to irregularities in the flow. Dimensional analysis of the flow strongly suggested that the unsteady nature of the flow was the dominant feature of the flowfield. Recommendations for future experimental work include the addition of valves and a mock circulatory loop, as well as the use of different settings for the LDV and PIV systems for different parts of the VAD and different parts of the cycle.
Keywords: Engineering, Mechanical.